Beneficiation of food processing by-products through extraction of bioactive compounds using neoteric solvents. (December 2020) - Saini, Anuradha; Panesar, Parmjit S.
Abstract: Food processing industries produce a huge amount of heterogeneous by-products in different processing operations while converting raw materials into final products. The extraction-based value addition of these by-products is an important step for waste minimization. In this context, it is desirable to approach greener extraction alternatives using smart solvents like ionic liquids and deep eutectic solvents. These solvents may potentially replace conventional solvents due to their biocompatibility, low toxicity and recyclability. Also, these solvents have tunable properties needed for specific selectivity of a particular bioactive compound. This paper delivers information regarding different types of neoteric solvents (fluorous solvents, ionic liquids and deep eutectic solvents) and their application in the extraction of high-value compounds from food processing by-products. Highlights: Neoteric solvents are efficient for the extraction of bioactive compounds. High extraction rate of bioactive compounds from food processing by-products. Neoteric solvents retain the properties of extracted compounds. Deep eutectic solvents and natural deep eutectic solvents are the green & safe solvents among neoteric solvents.